Peran Kepemimpinan dalam Memoderasi Pengaruh Beban Kerja dan Kepuasan Kerja terhadap Quiet Quitting - Sunur, Cisilia Sartifa; Pudjiastuti, Dini; Angesti, Nadya Ganis; Yulian, Muhammad Farhan; Setiadi, Nugroho Juli (JURNAL ILMIAH MANAJEMEN & BISNIS, 2025)
Purpose – This study aims to examine the influence of workload and job satisfaction on quiet quitting, with leadership as a moderating variable, among lecturers at private universities in Indonesia. Methodology – A quantitative approach with survey method was employed. Data were collected from 130 lecturers at a private university using a structured questionnaire and analyzed with Structural Equation Modelling–Partial Least Squares (SEM-PLS). Both direct relationships and the moderating effects of leadership were tested through interaction termsFindings – The results show that workload significantly increases quiet quitting, while job satisfaction does not have a significant effect on quiet quitting. Leadership moderates the relationship between workload and quiet quitting, but does not moderate the relationship between job satisfaction and quiet quitting.Originality/Value – By examining workload, job satisfaction, and leadership together, this study offers a fresh perspective on quiet quitting in higher education, introducing a moderation approach that remains rare in this context.Practical Implications – The findings suggest that managing workload effectively and investing in strong, supportive leadership are critical to reducing quiet quitting. Universities can use these insights to design leadership programs that not only ease the strain of heavy workloads but also foster conditions where lecturers remain engaged and committed.